2014
DOI: 10.1088/0963-0252/23/6/065035
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the similarity law for the glow discharges in non-plane-parallel gaps

Abstract: The glow discharges in the gaps geometrically similar to that used in glow discharge cleaning of the International Thermonuclear Experimental Reactor (ITER) were numerically simulated based on a two-dimensional fluid model in which the linear dimensions of gap A are two times that of gap B and the pressure of gap A is half that of gap B. Under an applied voltage of 1000 V, the physical parameters at the corresponding point pz in these two gaps were compared. It was found that the electric potential U (pz), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…It is assumed that electrons, excited atoms, and ions become attached to the surface of the non-cathode wall. 31,32 The electric potential u is obtained from u¼U 0 -IÁR b at the anode (where I is the total discharge current) and u ¼ 0 at the cathode.…”
Section: Model Descriptionmentioning
confidence: 99%
“…It is assumed that electrons, excited atoms, and ions become attached to the surface of the non-cathode wall. 31,32 The electric potential u is obtained from u¼U 0 -IÁR b at the anode (where I is the total discharge current) and u ¼ 0 at the cathode.…”
Section: Model Descriptionmentioning
confidence: 99%
“…30 This results from the similarity laws are more commonly applied in discharges in low-pressure regimes. [32][33][34][35][36] However, for the high-pressure discharges, some other physical mechanisms, such as three-body collisions and dissociative recombination, become considerable so that the applicability of the similarity law is not straightforward. No matter what the discharge mechanisms are, the requirements of the similarity law on the particle productions from different physical processes are the same, which can be generally derived from the similarity relations in Table I.…”
Section: Similarity Laws and Discharge Processesmentioning
confidence: 99%
“…In our previous studies, validity of the similarity law has been confirmed in the lowpressure discharges, where many other nonlinear processes, such as the three-body collision and recombination, are of less importance. [34][35][36]…”
Section: Similarity Laws and Discharge Processesmentioning
confidence: 99%
“…The relations between the physical quantities and some physical phenomena can not be explained strictly. Most authors use numerical methods in the theoretical study [7][8][9][10][11][12][13][14]. With the development of computer and algorithm optimization, these methods provide a good foundation and guarantee with great achievements made in this field.…”
Section: Introductionmentioning
confidence: 99%